What must be done to get toxin out of Kenya’s food supply - Hoffmann, Vivian (The Conversation, 2019)
An exposé in Kenya has revealed that there are high amounts of a poisonous substance, known as aflatoxin, in many of Kenya’s popular maize flour brands. This is particularly worrying as maize flour is a staple food for most Kenyans. Part of the problem is in how maize is processed and distributed in the country. Vivian Hoffmann shares her insights on this and what must be done to prevent it.